The Saudi Vision 2030: Reproduction of Women’s Empowerment in the Saudi Press: A Corpus-based Critical Discourse Analysis - Afzal, Naeem; Omar, Abdulfattah (Register Journal, 2021)
The Kingdom of Saudi Arabia has witnessed unprecedented reforms within the framework of the Saudi Vision 2030. However, despite prolific news reports related to economic, social, and political reforms associated with the Saudi Vision 2030, there is a general lack of studies on the ideological constructions of these reforms in the Saudi press. As thus, this study seeks to explore the news representation and ideological construction of the vision 2030 reforms in the Saudi press. It focuses on the reproduction of women’s empowerment in the Saudi press. For this purpose, a corpus of 1578 newspaper articles, reports, stories, and editorials published in Arab News and Saudi Gazette is designed. Analysis of the data is carried out through corpus-based critical discourse analysis (CDA) quantitatively and qualitatively through a concordance, frequency, collocates, and dispersion. Results indicated that the Saudi press, under its ideological orientation, reproduced the vision 2030 as a matter of public interest. Both newspapers exhibited a great inclination towards endorsing women’s empowerment as stipulated in the vision. The Saudi Vision’s representation of women’s empowerment was reflected and reproduced in many ways in newspapers’ articles, reports, stories, and editorials. This study was limited to the newspaper content released after the emergence of the Saudi Vision in 2016. Further research is recommended on the influence of the Saudi press on the representation of women’s rights discourse in the Saudi Vision 2030; it may also include the public opinion about such transformational reforms.Keywords: corpus-based CDA, discourse reproduction, newspaper representations, Saudi Vision 2030, women’s empowerment